Recognizing the Symptoms of Mental Illness following Concussions in the Sports Community: A Need for Improvement - Topolovec-Vranic, Jane (PLoS One, 2015)
OBJECTIVE: To evaluate the awareness of concussion-related symptoms amongst members of the sports community in Canada. METHODS: A cross-sectional national electronic survey was conducted. Youth athletes, parents, coaches and medical professionals across Canada were recruited through mailing lists from sports-related opt-in marketing databases. Participants were asked to identify, from a list of options, the symptoms of a concussion. The proportion of identified symptoms (categorized as physical, cognitive, mental health-related and overall) as well as participant factors associated with symptom recognition were analyzed. RESULTS: The survey elicited 6,937 responses. Most of the respondents (92.1%) completed the English language survey, were male (57.7%), 35–54 years of age (61.7%), with post-secondary education (58.2%), or high reported yearly household income (>$80,000; 53.0%). There were respondents from all provinces and territories with the majority of respondents from Ontario (35.2%) or British Columbia (19.1%). While participants identified most of the physical (mean = 84.2% of symptoms) and cognitive (mean = 91.2% of symptoms), they on average only identified 53.5% of the mental health-related symptoms of concussions. Respondents who were older, with higher education and household income, or resided in the Northwest Territories or Alberta identified significantly more of the mental health-related symptoms listed. INTERPRETATION: While Canadian youth athletes, parents, coaches and medical professionals are able to identify most of the physical and cognitive symptoms associated with concussion, identification of mental health-related symptoms of concussion is still lagging.